Experimental and numerical investigations on tensile properties of carbon fibre-reinforced plastic and self-reinforced polypropylene composites - Ma, Quanjin; Sahu, Santosh Kumar; Badgayan, Nitesh Dhar; Mohd Ruzaimi, Mat Rejab (Walter de Gruyter GmbH, 2024)
numerical investigations. The experimental study evaluated the tensile strength, tensile strain, and modulus of CFRP and SRPP composite laminates under tensile loading. Finite element modelling was employed to predict and validate the tensile properties of these composites. CFRP and SRPP laminates were manufactured using the hot compression technique and stacked through the hand lay-up technique. The results revealed that CFRP with a unidirectional pattern provided a higher tensile strength (1,162 MPa) than the twill pattern (288 MPa) with nominal strain values of 0.017 and 0.013 in the CFRP-based system, respectively. It was observed that the results of CFRP and SRPP composites provided a good agreement between experimental and numerical investigations. Moreover, the failure behaviour of CFRP and SRPP laminates was evaluated and compared with experimental and numerical results. Furthermore, practical applications of CFRP and SRPP composites for lightweight parts are presented.